Reinforcing and reinforcing repair method and repair material for debris flow protection structure and abrasion depth prediction method
By evaluating the depth of abrasion and formulating a reinforcement and reinforcement and repair strategy, and using composite repair materials for "both internal and external repair", the problem of low remediation in the existing technology is solved, and the impact and wear resistance of the mudslide protection structure is significantly improved.
Patent Information
- Application Number
- CN202510428586.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-04-08
AI Technical Summary
The prior art has low degree of refinement in the repair of mudslide protection structures, making it difficult to effectively repair two types of damage situations, including overall structural damage and surface damage, resulting in low construction quality.
By evaluating the abrasion depth of the mudslide protection structure, formulating reinforcement and repair strategies, and using composite repair materials for "both internal and external repair" to improve the overall strength and impact and wear resistance of the structure.
The fine repair of the mudslide protection structure has been achieved, which significantly improves its impact and wear resistance, extends its service life, and improves the construction quality.
Smart Images

Figure CN119956714A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of disaster prevention and mitigation engineering, and in particular to a reinforcement and repair method, a repair material and an abrasion depth prediction method for a debris flow protection structure. Background Art
[0002] Debris flow is a highly destructive natural disaster characterized by high velocity, high impact force and complex multiphase flow.
[0003] The main forms of damage caused by debris flows to protective structures such as sand dams and drainage channels can be divided into two categories: overall structural damage and surface damage. Overall structural damage is usually caused by the impact of debris flows and environmental factors that damage the base material of the protective structure. Under the coupling effect of debris flows and the environment (freeze-thaw environment, groundwater chemical erosion, etc.), the degradation of the mortar matrix, fiber breakage, and aggregate peeling will lead to a decrease in the overall strength of the protective structure. Surface damage is usually caused by the abrasion and erosion of the surface of the protective structure by solid particles in the debris flow. During the movement of the debris flow, the high-hardness particles it carries will cause abrasion or form erosion pits on the surface of the protective structure, reducing the protection of the base material. Therefore, the destruction or damage of the protective structure caused by debris flow disasters will shorten its service life, requiring regular maintenance or damage repair.
[0004] In the prior art, for example, the Chinese invention patent with the patent publication number CN114541337A discloses a method for repairing the damaged section of the debris flow drainage channel. After determining the abrasion damage area of the drainage channel, the aged and deteriorated concrete layer on the surface is chiseled off and roughened and cleaned to form a joint surface, the exposed steel bars on the joint surface are rust-removed and rust-proofed, the floating dust and loose aggregates on the joint surface are removed, a wire rope mesh is laid on the joint surface, and then the joint surface is cast and repaired with steel fiber concrete, so as to quickly repair the drainage channel and restore its silt removal function. However, such prior art usually determines the abrasion damage area of the drainage channel by experience or surface observation, and the repair method is relatively extensive.
[0005] Therefore, those skilled in the art hope to seek a better solution for repairing debris flow protection structures, which can perform more detailed repairs on both overall structural damage and surface damage, and improve construction quality. Summary of the invention
[0006] In view of the shortcoming of the low level of refinement of existing debris flow protection structure repair schemes, the present invention provides a series of schemes related to the reinforcement and reinforcement repair method, repair materials and abrasion depth prediction method of debris flow protection structures. A reinforcement and reinforcement repair strategy for debris flow protection structures is formulated according to the abrasion depth. At the same time, two types of damage, overall structural damage and surface destruction, are repaired to restore or enhance the strength and impact and wear resistance of the debris flow protection structure.
[0007] First, the present invention uses the abrasion depth as a key indicator for evaluating the wear resistance of materials, which is used to estimate the abrasion of debris flow protection structures and formulate reinforcement and repair strategies. Based on this technical concept, the present invention provides a repair method, repair material and abrasion depth prediction method for reinforcing and repairing debris flow protection structures.
[0008] Secondly, based on the concept of "repairing both inside and outside", the present invention achieves the dual effects of overall damage control and surface abrasion protection through composite repair materials, thereby comprehensively improving the strength and impact and wear resistance of the debris flow protection structure.
[0009] The specific plan is as follows, involving the reinforcement and repair methods, repair materials and abrasion depth prediction methods of debris flow protection structures.
[0010] First, the present invention provides a method for reinforcing and repairing a debris flow protection structure. The repair method first evaluates the surface abrasion depth of the protection structure to formulate a reinforcement and repair strategy; according to the reinforcement and repair strategy, when implementing the repair project, the construction area is cleaned, and the matrix reinforcement material is poured into the construction area to allow it to penetrate into the base material of the protection structure to repair or enhance the ability to resist overall structural damage; then a surface wear-resistant layer is added to the surface of the base material to repair or enhance the ability to resist surface damage.
[0011] Furthermore, the surface wear-resistant layer is made of a hard iron sheet layer, and the hard iron sheet is pasted on the surface of the substrate during construction.
[0012] Furthermore, the surface wear-resistant layer is formed by curing polyurea coating. During construction, the polyurea coating is sprayed on the surface of the substrate, or a plurality of polyurea blocks are fixed on the surface of the substrate in a bionic arrangement to form a bionic structure. Spraying the polyurea coating on the surface of the substrate is equivalent to full coverage; using the bionic structure to perform surface structuring on the substrate is equivalent to partial coverage.
[0013] Furthermore, the bionic structure adopts a boss structure; The boss structure is composed of a plurality of parallel long convex strips that are raised relative to the surface of the substrate, and the convex strips are arranged horizontally relative to the flow direction of the debris flow; the convex strips in this structure are polyurea blocks pressed by a mold; Furthermore, the bionic structure adopts a wire slot structure; The wire trough structure is composed of a plurality of parallel long square strips that are recessed relative to the surface of the substrate, and the square strips are arranged horizontally relative to the flow direction of the debris flow; the square strips in this structure are polyurea blocks pressed by a mold; Furthermore, the bionic structure adopts a ball-groove structure; The ball groove structure is formed by arranging a plurality of hemispherical bodies in a matrix which are recessed relative to the surface of the substrate; the hemispherical bodies in this structure are polyurea blocks pressed by a mold; Furthermore, the bionic structure adopts a mesh structure; The mesh structure is formed by arranging a plurality of square blocks in a matrix which are recessed relative to the surface of the substrate; the square blocks in this structure are polyurea blocks pressed by a mold.
[0014] Furthermore, when the boss structure is used for surface structuring, the convex strip-shaped polyurea blocks are directly cured on the surface of the substrate.
[0015] Furthermore, when any bionic structure of the line groove structure, ball groove structure, or mesh groove structure is used for surface structuring, a groove structure is reserved on the surface of the substrate according to the structure and arrangement of the polyurea blocks, and then the polyurea blocks are embedded in the groove structure.
[0016] Furthermore, the matrix reinforcement material includes coarse aggregate and mortar; the gradation distribution of the coarse aggregate conforms to the Andreasen & Andersen model, and the distribution modulus q is 0.19; the mortar is composed of P·I type 42.5 grade silicate cement, microsilica fume, ISO standard sand, steel fiber, water reducer and water. Among them, the steel fiber is one or more of copper-plated steel fiber, end hook steel fiber and milling steel fiber.
[0017] Furthermore, the steel fiber is copper-plated steel fiber or end-hook steel fiber, and the amount of the steel fiber is 1% of the overall volume ratio.
[0018] Second, the present invention provides a reinforcing and repairing material for a debris flow protection structure. The repairing material comprises a matrix reinforcing material and a surface wear-resistant material; The matrix reinforcement material can penetrate into the base material of the protective structure to enhance the resistance and reduce the overall structural damage caused by debris flow impact and environmental factors; The surface wear-resistant material can be covered on the surface of the protective structure to enhance the resistance and reduce the surface damage caused by the scouring of particles in the debris flow.
[0019] Furthermore, the present invention uses concrete mainly composed of coarse aggregate and mortar as the matrix reinforcement material. The particle size of the particles in the matrix reinforcement material is small and can penetrate into the base material of the debris flow protection structure, and the overall impact resistance is improved through mortar matrix reinforcement and fiber reinforcement treatment.
[0020] In order to enhance the abrasion resistance of the debris flow protection structure after repair, it is necessary to design the coarse aggregate and mortar in the matrix reinforcement material.
[0021] The gradation distribution of the coarse aggregate conforms to the Andreasen & Andersen model, and the distribution modulus q is 0.19. The common raw material of the coarse aggregate is crushed limestone, and the content of the coarse aggregate in each cubic meter of the matrix reinforcement material is 650kg-670kg.
[0022] The grading curve of coarse aggregate is calculated by the following formula 1, formula 2, and formula 3: (Formula 1) (Formula 2) (Formula 3) In the formula, P ( D ) indicates that the particle size is smaller than the particle size D Cumulative fraction of total solids; All with D The relevant parameters are all related to the particle size, unit: mm; among them, , , Superscript q is the distribution modulus, which is used to control the shape of the grading curve. The smaller the value, the higher the proportion of fine aggregate. Here, the value is 0.19; Represents the distribution modulus q The corresponding aggregate particle size; Represents the distribution modulus q The corresponding minimum particle size of aggregate; Represents the distribution modulus q The corresponding maximum particle size of aggregate; RSS stands for residual sum of squares, which indicates the difference between the actual gradation and the target gradation; n Indicates the total number of particle size intervals; i The number indicating the particle size interval; Indicates the particle size interval segmentation; Indicates that the designed graded mixture is within the particle size range Cumulative percentage of Indicates that the target graded mixture is in the same particle size range The cumulative percentage is calculated by formula 1; R 2 It represents the fitting coefficient, with a value range of [0, 1], which is used to evaluate the degree of fit between the design gradation distribution and the target gradation distribution. The closer the value is to 1, the better the fitting effect is, and the closer the value is to 0, the worse the fitting effect is.
[0023] Among them, Formula 2 uses the least squares method to optimize the fitting degree between the design gradation curve and the target gradation curve, and Formula 3 uses the fitting coefficient R 2 Quantify the degree of match.
[0024] The mortar consists of P·I type 42.5 grade silicate cement, microsilica fume, ISO standard sand, steel fiber, water reducing agent and water.
[0025] As the main bonding material in mortar, silicate cement bonds other components together and provides the basis for early and late strength. The 42.5 strength grade indicates that the 28-day compressive strength is ≥42.5 MPa, its specific surface area is 3550 cm² / g, and its density is 3.12 g / cm³, which is the key source of the mechanical properties of mortar.
[0026] ISO standard sand, as a fine aggregate, can assist coarse aggregate in building a rigid skeleton, reduce cracks generated during cement hydration or drying, and disperse the load, indirectly improving the toughness of the material.
[0027] Microsilica fume has a very fine particle size, generally 0.1-0.2μm, which can fill the gaps between particles, improve density, and be used to refine the microstructure of concrete; microsilica fume produces volcanic ash reaction in mortar to generate additional gel, which cooperates with cement to enhance the bonding performance between steel fiber and substrate, and enhances the later strength and durability. The SiO2 content of commonly used microsilica fume is 92.3%, and the specific surface area is 19.1 m² / g.
[0028] Steel fibers delay the expansion by bridging cracks, improving the tensile strength, impact resistance and toughness of mortar, and play a role in crack resistance and toughness enhancement; after steel fibers are added to the base material, brittle fracture is transformed into ductile failure, and the structural safety is improved by changing the failure mode. Usually, steel fibers are one or more of copper-plated steel fibers, end hook steel fibers, and milling steel fibers.
[0029] Water reducer is used to reduce the water-binder ratio and improve the fluidity loss problem caused by high content of microsilica fume. Usually, polycarboxylic acid water reducer is used, with a solid content of 50% and a dosage of 0.5% to 1.5% of the mass of the adhesive material.
[0030] Therefore, cement, microsilica fume, steel fiber, ISO standard sand, steel fiber and water reducing agent form a synergistic effect.
[0031] Furthermore, the surface wear-resistant material is polyurea coating or iron sheet.
[0032] First, particle cutting, microcracks, scratches, and indentations are the main reasons for damaging the surface concrete of debris flow protection structures. Through research and testing, it was found that using polyurea coatings, polyurethane waterproof coatings, iron sheets, and rubber for surface treatment of debris flow protection structures can improve the abrasion resistance, erosion resistance, and bending strength of concrete; among them, the wear rates of concrete treated with polyurea coatings and iron sheets within 48 hours were 0.04 g / h and 0.03 g / h, respectively, which were 75% and 81% lower than those of concrete without surface treatment, respectively, showing better impact resistance and scratch resistance, becoming the preferred solution.
[0033] Therefore, when performing surface treatment on the debris flow protection structure, the polyurea coating can be sprayed on the surface of the protection structure to form a polyurea layer. Of course, a hard iron sheet layer can also be selected as the surface wear-resistant layer according to actual conditions, and the hard iron sheet can be pasted on the surface of the protection structure during construction.
[0034] Polyurea layer thickness D PUA The average particle size D4 of debris flow particles satisfies: D PUA ≤ D4 / 5.4 (Formula 4) Thickness of iron sheet D IS The average particle size D4 of debris flow particles satisfies: D IS ≤ D4 / 33.2 (Formula 5) During construction, the thickness of the polyurea layer can be designed according to Formula 4, and the thickness of the iron sheet layer can be designed according to Formula 5.
[0035] Compared with the polyurea layer formed by polyurea coating, iron sheet is a hard layer with higher compressive strength, low cost and easy to implement adhesive construction, but it also has disadvantages. The adhesion between iron sheet and substrate is relatively weak, it is easy to loosen or fall off, and the service life is short; iron sheet is difficult to adapt to complex curved surfaces or irregular surfaces, and needs to be cut and spliced during construction; iron sheet is easy to rust in humid or corrosive environments and needs regular maintenance; iron sheet has a large density, which increases the deadweight of the protective structure. Compared with hard iron sheet, polyurea coating is a tough coating with high raw material cost, and construction requires professional equipment and technicians. However, polyurea coating has excellent physical and chemical properties such as high strength, high elongation, high wear resistance, and high aging resistance. In addition, polyurea coating has a fast curing speed and can be sprayed on any curved surface, inclined surface and vertical surface without sagging. The coating is continuous, dense and seamless, so its protective performance is outstanding. In the actual construction process, the staff can make a choice according to construction requirements, construction conditions and other factors.
[0036] Although polyurea coatings have better comprehensive protection than iron sheets, the overall coating method on the surface of debris flow protection structures requires a large amount of polyurea coating and is costly.
[0037] In order to reduce the amount of polyurea coating as much as possible while improving the impact resistance and abrasion resistance of the surface of the debris flow protection structure, the present invention proposes a solution for surface structuring of the polyurea layer, and replaces the polyurea layer with polyurea blocks arranged in a biomimetic manner. Compared with the polyurea layer that fully covers the surface of the substrate, the polyurea blocks that only partially cover the surface of the substrate can not only ensure abrasion resistance, but also effectively reduce the amount of polyurea coating.
[0038] Specifically, before the polyurea coating is formed, a mold is used to press out four types of polyurea blocks, namely, convex strips, square strips, hemispheres, and square blocks, and a number of polyurea blocks are arranged bionic on the surface of the substrate, thereby forming corresponding boss structures, line groove structures, ball groove structures, and net groove structures. The convex strips are convex relative to the surface of the substrate, and the square strips, hemispheres, and square blocks are all concave relative to the surface of the substrate. The boss structure is composed of a plurality of long strips of convex strips arranged in parallel, and the line groove structure is composed of a plurality of long strips of square strips arranged in parallel. Both are stripe structures, but one is convex and the other is concave relative to the surface of the substrate.
[0039] Usually, ignoring the influence of processing and construction accuracy, the height of the convex strip is equal to the height of the convex strip exceeding the surface profile of the substrate, the height of the square strip is equal to the depth of the square strip sunk into the surface profile of the substrate, the height of the round bottom of the hemisphere is equal to the depth of the hemisphere sunk into the surface profile of the substrate, and the height of the square block is equal to the depth of the square bar sunk into the surface profile of the substrate. The first point to be explained is: as a standard hemisphere, the height of the round bottom is equal to the radius of the hemisphere; although it is difficult to process a standard hemisphere in actual processing, the radius of the hemisphere is still used as the height of the round bottom of the hemisphere when calculating parameters; when installed, the circular plane of the hemisphere is flush with the surface profile of the substrate, and usually several hemispheres are distributed in rows and columns with equal spacing. The second point to be explained is: the length and width of the convex strips and square strips are relatively large, and usually the length of the convex strips and square strips is equal to the width of the debris flow protection structure and is distributed at equal spacing. The third point to be explained is: the length-to-width ratio of the block is 1, and usually several blocks are distributed in rows and columns with equal spacing.
[0040] In order to conveniently describe the structure and distribution structure of the polyurea block, the height of the convex strip, the height of the square strip, the height of the round bottom of the hemisphere, and the height of the square are recorded as the block height D1, the distance between adjacent convex strips, the distance between adjacent square strips, the distance between adjacent hemispheres, and the distance between adjacent squares are recorded as the block spacing D2, and the width of the convex strip, the width of the square strip, the circular surface diameter of the hemisphere, and the width of the square are recorded as the block width D3.
[0041] At this time, the relationship between the block height D1, the block spacing D2, the block width D3 and the average particle size D4 of the debris flow particles satisfies: D1 ≥ D4 / 1.2 (Formula 6) D2≤ 2D3 (Formula 7) D2 ≥ D4 (Formula 8) The ribs and grooves arranged in the bionic structure are arranged perpendicular to the flow direction of the debris flow. It should be noted that the flow direction of the debris flow is the overall flow direction described in a macroscopic way, not an absolute direction; the vertical relationship here is also generalized, not absolutely 90°, and usually a deviation within 10 degrees can be considered a vertical relationship. Furthermore, the flow direction of the local location where the debris flow passes may deviate greatly from the overall flow direction. Therefore, in actual construction, striped structures such as ribs and grooves are not placed along the flow direction of the debris flow, but can be placed horizontally with the flow direction of the debris flow.
[0042] Third, the present invention provides a method for predicting the abrasion depth of a debris flow protection structure. The prediction method estimates the abrasion depth based on the structural density of the debris flow protection structure, the duration of the debris flow, the abrasion coefficient and the correction coefficient, and is used to implement the reinforcement and repair method of the debris flow protection structure.
[0043] Furthermore, the value of the correction coefficient is obtained by calculating two sets of parameters related to the volume content, density, particle size and flow velocity of solid particles in the debris flow parameters and the laboratory test parameters.
[0044] It should be noted that the repair method and repair material described in the present invention are not only used to repair the damaged area of the debris flow protection structure, but also used to enhance the protective performance of the debris flow protection structure, and can be used for both post-repair and pre-protection. Moreover, the repair method and repair material described in the present invention are not only used to repair or enhance the overall strength of the debris flow protection structure, but also to compositely strengthen and enhance the performance of the protection structure through surface property enhancement treatment, thereby achieving overall damage control and surface abrasion protection.
[0045] It should also be noted that the abrasion depth prediction method described in the present invention is mainly used to predict the abrasion depth of materials caused by debris flow. The predicted abrasion depth can be used to determine the timing of repair, determine the area to be constructed, select the parameters of the repair material, etc., so as to formulate a reinforcement and reinforcement repair strategy.
[0046] Therefore, by first quickly evaluating the abrasion depth on site through the abrasion depth prediction method described in the present invention, and then combining the overall damage control and surface abrasion protection technology, the impact and abrasion resistance of the debris flow protection structure can be repaired or improved. It can be widely used in debris flow protection structures such as sand dams and drainage channels, as well as other water conservancy and transportation infrastructure projects that require impact and abrasion resistance, thereby providing technical support for the reinforcement of mountain disaster prevention and control projects.
[0047] The beneficial effects of the present invention are as follows.
[0048] (1) The reinforcement and repair method for debris flow protection structure provided by the present invention uses the abrasion depth as a key indicator for evaluating the wear resistance of the material, and formulates the reinforcement and repair strategy for the debris flow protection structure according to the abrasion depth, so as to obtain a more accurate and economical repair plan.
[0049] (2) The reinforcement and repair method for debris flow protection structure provided by the present invention uses composite repair materials to "repair both the inside and the outside" of the debris flow protection structure, achieving the dual effects of overall damage control and surface abrasion protection, and comprehensively improving the strength and impact and wear resistance of the debris flow protection structure.
[0050] (3) The reinforcement and repair method for debris flow protection structure provided by the present invention can significantly improve the impact resistance and abrasion resistance of the debris flow protection structure, and provide technical support for the reinforcement and reinforcement of mountain disaster prevention and control projects.
[0051] (4) The reinforcing and repairing material for debris flow protection structure provided by the present invention is mainly composed of matrix reinforcement material and surface wear-resistant material. It can penetrate into the base material of the protection structure to enhance the overall strength and improve the overall impact resistance. It can also form a surface wear-resistant layer on the surface to enhance the surface's resistance to abrasion and erosion.
[0052] (5) The method for predicting the abrasion depth of debris flow protection structures provided by the present invention can accurately estimate the abrasion depth, providing an important reference for formulating strategies for reinforcing and repairing debris flow protection structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 It is a schematic diagram of the principle of the reinforcement and repair method of the debris flow protection structure in the present invention.
[0054] Figure 2 Schematic diagram of the abrasion coefficient fitting curve.
[0055] Figure 3 It is the abrasion rate of samples with sample numbers Ref.1, S1, M1, L1, M0.5, and M1.5.
[0056] Figure 4 It is the abrasion depth of samples with sample numbers Ref.1, S1, M1, L1, M0.5, and M1.5.
[0057] Figure 5 Schematic diagram of various types of surface wear-resistant layers of debris flow protection structures.
[0058] Figure 6 The abrasion time and abrasion rate of four groups of samples with sample numbers Ref.2, PUA, IS, and RB.
[0059] Figure 7The abrasion time and abrasion rate of the PUR sample with sample number.
[0060] Figure 8 It is a schematic diagram of the structure of the sample Convex; Figure 8 (a) is the top view of the sample Convex bionic structure. Figure 8 (b) is the side view of the Convex bionic structure sample.
[0061] Fig. 9 is a schematic diagram of the structure of the sample Parallel; Fig. 9 (a) is the top view of the sample Parallel bionic structure. Fig. 9 (b) is the side view of the sample Parallel bionic structure.
[0062] Fig.10 is a schematic diagram of the structure of the sample Circle; Fig.10 (a) is the top view of the sample Circle bionic structure. Fig.10 (b) is the side view of the Circle bionic structure of the sample.
[0063] Fig.11 It is a schematic diagram of the structure of the sample Net; Fig.11 (a) is the top view of the sample Net bionic structure. Fig.11 (b) is the side view of the sample Net bionic structure.
[0064] Fig.12 Schematic diagram of mass loss of sample Ref.3, sample Convex, sample Parallel, sample Circle, and sample Net after 24 hours of abrasion.
[0065] Fig.13 This is a schematic diagram of the compressive strength and flexural strength test results of the Convex, Parallel, Circle, and Net samples after 24 hours of abrasion. Fig.13 (a) is a schematic diagram of the compressive strength test results. Fig.13 (b) is a schematic diagram of the bending strength test results.
[0066] Fig.14 Schematic diagram of mass loss of Parallel specimen and Convex specimen after 24 hours of abrasion when the block width and block spacing are designed to be 4mm, 6mm, and 8mm.
[0067] Fig.15 The schematic diagram of the compressive strength and flexural strength test results of Parallel and Convex specimens after 24 hours of abrasion when the block width and block spacing are designed to be 4mm, 6mm, and 8mm, where: Fig.15(a) is a schematic diagram of the compressive strength test results. Fig.15 (b) is a schematic diagram of the bending strength test results.
[0068] Fig.16 The schematic diagram is a schematic diagram of the principle when the surface of sample Ref.3, sample Convex, sample Parallel, sample Circle, and sample Net is washed by solid particles in the debris flow, where: Fig.16 (a) is the surface abrasion of sample Ref.3. Fig.16 (b) is the surface abrasion of the Convex sample. Fig.16 (c) is the surface abrasion of the parallel sample. Fig.16 (d) is the surface abrasion of the sample Circle. Fig.16 (e) is the surface abrasion of the sample Net.
[0069] Fig.17 The surface morphology of the five groups of samples, Ref.3, Convex, Parallel, Circle, and Net, after 24 hours of abrasion. Fig.17 (a) is the surface wear morphology of sample Ref.3. Fig.17 (b) is the surface erosion morphology of the Convex sample. Fig.17 (c) is the surface wear morphology of the parallel sample. Fig.17 (d) is the abrasion morphology of the sample Circle surface. Fig.17 (e) is the surface abrasion morphology of the sample Net.
[0070] In the figure, 1. Surface damaged by abrasion; 2. Substrate damaged by impact; 3. Surface wear-resistant materials; 3.1. Flat surface wear-resistant layer; 3.2. Bionic structure; 4. Matrix reinforcement material; 4.1. Fiber reinforcement; 4.2. Densely packed aggregate. DETAILED DESCRIPTION
[0071] The above contents of the present invention are further described in detail below in conjunction with the specific implementation methods of the embodiments. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. Various substitutions or changes made according to common technical knowledge and customary means in the art without departing from the above technical ideas of the present invention should be included in the scope of the present invention.
[0072] Embodiment 1: like Figure 1As shown, the debris flow protection structure has been severely damaged by the debris flow disaster, and the abrasion-damaged surface 1 and the impact-damaged substrate 2 need to be repaired. This embodiment proposes a method for reinforcing and reinforcing the debris flow protection structure. First, the abrasion depth of the surface of the protective structure is evaluated to formulate a reinforcement and reinforcement repair strategy, and the repair material is used for repair construction. According to the reinforcement and reinforcement repair strategy, when implementing the repair project, the construction area is cleaned, and the matrix reinforcement material 4 is poured into the construction area to be constructed so that it penetrates into the substrate of the protective structure. The matrix reinforcement material 4 penetrates into the substrate of the debris flow protection structure, and steel fibers are used as fiber reinforcements 4.1. Coarse aggregates and fine aggregates form densely packed aggregates 4.2, which are used to repair or enhance the ability to resist overall structural damage; then, a surface wear-resistant material 3 is used to form a surface wear-resistant layer on the surface of the protective structure, which is used to repair or enhance the ability to resist surface damage.
[0073] Common construction steps are as follows: Step S1, construction preparation: clean the surface of the debris flow protection structure, remove loose materials and debris; measure and mark the area to be constructed according to the design drawings; Step S2, construction of matrix reinforcement material 4: prepare matrix reinforcement material 4 according to the designed ratio, mix it evenly and pour it into the area to be repaired; use vibration equipment to remove bubbles to ensure the matrix is dense; and cure it at room temperature for 28 days; Step S3, construction of surface wear-resistant material 3: after the substrate is cured, spray polyurea material or paste a hard iron layer; if bionic treatment is designed, use a mold to process polyurea blocks and fix them on the surface of the concrete substrate to form a bionic arrangement; Step S4, construction acceptance and post-maintenance: Use a 3D scanner to check the uniformity of the surface wear-resistant layer and the integrity of the bionic structure 3.2; regularly check the wear of the surface wear-resistant layer, and add spraying or repair when necessary.
[0074] The reinforcement and repair strategy described in the present invention includes, but is not limited to, determining the timing of repair, determining the area to be constructed, and selecting parameters for repair materials.
[0075] First, the depth of abrasion can qualitatively reflect the degree to which a region is affected by debris flow disasters and the importance of repair and protection. If the depth of abrasion has exceeded the warning threshold, emergency repair and protection work needs to be carried out as soon as possible; if the depth of abrasion has not exceeded but is close to the warning threshold, it is necessary to plan to carry out preventive repair and protection work in the short term; if the depth of abrasion is within the warning threshold and is far less than the warning threshold, daily maintenance is sufficient during the period of low incidence of debris flow disasters, and the inspection frequency is increased during the period of high incidence of debris flow disasters, and preventive repair and protection work is carried out according to the early warning situation. The above-mentioned circumstances for determining the timing of repair are only general experience, and staff can also confirm the timing of repair according to actual conditions.
[0076] 2. The structural density and structural abrasion coefficient of debris flow protection structures in different areas may not be exactly the same. When debris flows through different areas, debris flow parameters such as solid phase particle volume content, density, particle size, flow rate, duration, etc. may not be exactly the same. The depth of abrasion in different areas usually varies. Therefore, considering the economic benefits of saving resources, areas that have already undergone severe abrasion or are expected to undergo severe abrasion are usually included in the area to be constructed for repair during post-repair or pre-protection. In this way, the staff can confirm the area to be constructed based on the depth of abrasion, and the site selection method is more scientific.
[0077] Third, the specific material selection and proportion of each component in the repair material are different, which not only affects the abrasion coefficient of the repair material itself, but also affects the performance of the debris flow protection structure after the repair construction. Areas with greater abrasion depth often require the selection of repair materials with greater abrasion coefficients, or repair materials that can increase the density of the repaired structure. Therefore, knowing the abrasion depth is conducive to determining the specific substances of each component in the repair material and determining the proportion of each component in the repair material.
[0078] Fourth, knowing the overall abrasion depth of the area to be constructed can provide a scientific basis for estimating the workload and the amount of repair materials before construction, which can make the construction schedule more compact and the material use more standardized, which is conducive to improving the economic benefits of the project.
[0079] To sum up, this embodiment is based on the on-site rapid assessment method of abrasion depth. By combining overall damage control and surface abrasion protection technology, it can achieve a significant improvement in the impact resistance and abrasion resistance of debris flow protection structures, provide technical support for the reinforcement of mountain disaster prevention and control projects, and can be widely used in debris flow protection structures such as sand dams and drainage channels, as well as other water conservancy and transportation infrastructure projects that require impact resistance and abrasion resistance.
[0080] Embodiment 2: This embodiment describes in detail a method for predicting the abrasion depth of a debris flow protection structure.
[0081] Abrasion depth prediction is also an abrasion depth assessment. Abrasion depth assessment of debris flow protection structures is a key step in formulating reinforcement strategies. The abrasion depth prediction method for debris flow protection structures provided in this embodiment estimates the abrasion depth based on the structural density of the debris flow protection structure, the duration of the debris flow, the abrasion coefficient, and the correction coefficient, and is used to implement the reinforcement and repair method for the debris flow protection structure described in Example 1.
[0082] The sample was abraded using the wear resistance test device disclosed in the Chinese invention patent with patent publication number CN113390745A. Abrasive parameters used in the test: solid phase particle volume content V 0 is 30%, density ρ 0 is 2000 kg / m3 , average particle size of solid particles D 0 is 0.015 m and speed u 0 is 3 m / s, and then the compressive strength of the sample is measured, and the relationship between the compressive strength and the abrasion coefficient is obtained by fitting, such as Figure 2 shown.
[0083] Furthermore, this embodiment provides a method for quickly estimating the abrasion coefficient. Specifically, the abrasion coefficient is quickly estimated using the compressive strength value through Formula 9: (Formula 9) In the formula, k Indicates the abrasion coefficient, unit: kg / h / m 2 , used to characterize the abrasive mass loss of materials per unit time and per unit area; f c Indicates compressive strength, unit: MPa.
[0084] Furthermore, this embodiment provides a method for quickly calculating the correction coefficient. The correction coefficient is calculated according to equation 10 based on two sets of parameters related to the volume content, density, particle size, and flow velocity of solid particles in the debris flow parameters and the laboratory test parameters: (Formula 10) In the formula, a It represents the correction coefficient, which is used to adjust the difference between the indoor abrasive parameters and the actual debris flow parameters during the abrasion coefficient test; are debris flow parameters, representing the volume content of solid particles in debris flow (unit: %), the density of solid particles in debris flow (unit: kg / m 3 ), particle size of debris flow solid particles (unit: m), flow velocity of debris flow solid particles (unit: m / s); These are laboratory test parameters, representing the volume content of abrasive solid particles (unit: %), the density of abrasive solid particles (unit: kg / m 3 ), particle size of abrasive solid phase particles (unit: m), flow rate of abrasive solid phase particles (unit: m / s).
[0085] Finally, according to formula 11, the erosion depth is estimated by combining the density of protective structures and the duration of debris flow: (Formula 11) In the formula, E h Indicates the abrasion depth, unit: m; kIndicates the abrasion coefficient, which indicates the abrasion mass loss per unit area per unit time, unit: kg / h / m 2 ; ρ c Indicates structural density, unit: kg / m 3 ; t Indicates duration, unit: h; a Indicates the correction factor.
[0086] Embodiment 3: This embodiment describes the repair material in detail based on the embodiment 1.
[0087] The repair material includes a matrix reinforcement material 4 and a surface wear-resistant material 3. The matrix reinforcement material 4 can penetrate into the base material of the protective structure to repair or enhance the ability to resist overall structural damage. The surface wear-resistant material 3 can cover the surface of the protective structure to repair or enhance the ability to resist surface damage.
[0088] In one embodiment, the gradation distribution of the coarse aggregate conforms to the improved Andreasen & Andersen model, and the distribution modulus is q The value is 0.19. Limestone crushed stone with a maximum particle size of 9.5 mm is used as coarse aggregate. The mortar is composed of P·I type 42.5 grade silicate cement, microsilica fume, ISO standard sand, steel fiber, water reducer and water, wherein the water reducer adopts a polycarboxylic acid type high-efficiency water reducer with a solid content of 50%. The contents of coarse aggregate, silicate cement, microsilica fume, ISO standard sand, water reducer and water in each cubic meter of matrix reinforcement material 4 are 661kg, 450kg, 50kg, 640kg, 5kg and 125kg respectively, and the steel fiber is any one of copper-plated steel fiber, end hook steel fiber and milling steel fiber, and the addition amount accounts for 0.5% to 1.5% of the total volume.
[0089] All samples in this example were prepared according to the conventional concrete casting method (GB / T 50080-2016), demolded after 24 hours, and then cured in water at a temperature of 20±2°C until the test age. The samples were tested for mechanical properties, abrasion resistance, microstructure, and surface wear.
[0090] When conducting mechanical property tests, according to the EN 196-1 standard, the compressive strength and flexural strength of the 40×40×160 mm³ sample at 28 days of age were tested, with loading rates of 2400 N / s and 50 N / s respectively; according to the EN12390-6 standard, the splitting tensile strength of the 100×100×100 mm³ sample at 28 days of age was tested, with a loading rate of 0.05 MPa / s. The average value of the three samples was recorded as the test result. When conducting the anti-abrasion performance test, the sample was abraded using the wear resistance test device disclosed in the Chinese invention patent with patent publication number CN113390745A. The wear morphology of the sample after 24 hours, 48 hours, 72 hours, and 96 hours of wear was observed, the wear amount was obtained by weighing, and the wear depth was obtained by fixed-point measurement for evaluating the wear performance. Due to the difference in wear morphology, it is difficult to determine the wear height of each point on the sample surface. Therefore, three fixed points along the length direction of the sample surface: 40 mm, 80 mm, and 120 mm were selected as measurement points for wear depth measurement, and a vernier caliper with an accuracy of 0.01 mm was used for measurement. When observing the microstructure and surface wear, the surface morphology of the concrete sample was scanned by a 3D scanner (SHINING 3D, EinScan Pro 2X), and the concrete surface with wear time of 24 hours, 48 hours, 72 hours, and 96 hours was recorded using a high-definition camera. The original worn surface was analyzed using image analysis software (Image J) to obtain the pores and exposed aggregates on the worn surface; a scanning electron microscope (SEM) analyzer (Thermo Scientific, Apreo 2) was also used to analyze the microstructure of the worn concrete surface and the worn fibers.
[0091] The first type of experiment studies the effects of three different types of steel fibers, namely copper-plated steel fibers, end hook steel fibers, and milled steel fibers, and their different contents on the wear resistance of matrix reinforcement material 4.
[0092] The properties of three different types of steel fibers are shown in Table 1: Table 1 Characteristics of steel fibers Multiple groups of samples were designed by the control variable method with different types and amounts of steel fibers and the same other components. Six groups of typical samples were selected for explanation in combination with the experimental results. The six groups of samples were numbered R, S1, M1, L1, M0.5, and M1.5, respectively. The proportions of the components of each sample are shown in Table 2: Table 2 Ratio of each component of typical matrix reinforcement material samples The sample numbered Ref.1 is a sample without fiber added, which is used as a reference group. In the sample numbers S1, M1, L1, M0.5, and M1.5, the letters represent the fiber type, S represents copper-plated steel fiber, M represents hook-end steel fiber, and L represents milling steel fiber; the numbers represent the amount of steel fiber, that is, the volume ratio of steel fiber.
[0093] It should be noted that 661 kg of coarse aggregate is a mixture of 367 kg of aggregate with a particle size of 2.36-4.75 mm, 173 kg of aggregate with a particle size of 4.75-7 mm, and 121 kg of aggregate with a particle size of 7-9.5 mm.
[0094] Limestone is the most common gravel particle in southwest my country. Therefore, during the test, gravel with a particle size of 13.2mm-20mm and an average particle size of 16.6mm was selected to simulate the solid particles in the debris flow; the proportion of the debris flow abrasive material is shown in Table 3: Table 3 Proportions of debris flow abrasive materials The gravel particles were 2120 g, accounting for 20% of the total volume of debris flow materials, and the soil and water ratio (S / W) was 1:1 by mass.
[0095] The results of the anti-abrasion performance test are as follows: Figure 3 , Figure 4 As shown in the figure, first compare the three groups S1, M1, and L1. The steel fiber dosage is 1%, and the copper-plated steel fiber corresponding to S1 and the hook-end steel fiber corresponding to M1 have lower abrasion rate and abrasion depth, indicating that they have better wear resistance than the milling steel fiber corresponding to L1. Then compare the three groups M0.5, M1, and M1.5. The dosage of the three groups of hook-end steel fibers is different. The higher the content of hook-end steel fibers in the sample, the slower the abrasion rate and the smaller the abrasion depth. Further, the compressive strength, flexural strength, and tensile strength of the M1.5 concrete sample are 102.6 MPa, 19.28 MPa, and 9.56 MPa, respectively, which are 62.9%, 64.5%, and 84.2% higher than those of the reference group, respectively. Compared with compressive strength, tensile strength is considered to be a suitable indicator for evaluating the wear resistance of concrete. It can be seen that the matrix reinforcement material 4 with hook-end steel fibers exhibits better tensile strength, energy absorption capacity and residual strength, which may help to improve the resistance of concrete to the collision and friction of coarse solid particles in debris flows.
[0096] The second type of test selected polyurea coating, polyurethane waterproof coating, iron sheet and rubber to treat the surface of debris flow protection structure respectively. Figure 5 As shown, four types of surface wear-resistant layers are formed, namely, polyurea layer PUA, polyurethane layer PUR, hard iron layer IS, and flexible layer RB, and the influence of different surface wear-resistant materials 3 on the surface wear resistance of concrete protective structure is studied.
[0097] It should be noted that in the second type of test, the polyurea layer PUA, the polyurethane layer PUR, the hard iron layer IS, and the flexible layer RB are all flat surface wear-resistant layers 3.2, covering the surface of the sample.
[0098] The characteristic parameters of four different types of surface wear-resistant layers are shown in Table 4: Table 4 Characteristic parameters of different types of surface wear-resistant layers The dimensions of each specimen are 40mm×40mm×160 mm. The specimen numbered Ref.2 is a specimen without a surface wear-resistant layer and is used as a reference group. The overall height of all specimens is 40mm. The substrate height is the height of the concrete substrate itself when the thickness of the surface wear-resistant layer is not calculated. The thickness of the surface wear-resistant layer is the height of the surface wear-resistant layer of different materials. Therefore, the total height of the specimen numbered Ref.2 is equal to the substrate height, while the total height of the specimens numbered PUA, PUR, IS, and RB is the sum of the substrate height and the surface wear-resistant thickness. The substrate mass is the mass of the concrete substrate plus the mass of the surface wear-resistant layer, which is equal to the total mass of the specimen.
[0099] Gravel with a particle size of 13.2 mm to 20 mm and an average particle size of 16.6 mm is still selected to simulate the solid particles in the debris flow; the proportion of the debris flow abrasive material is shown in Table 5: Table 5 Proportions of debris flow abrasive materials The gravel particles were 3180 g, accounting for 30% of the total volume of debris flow materials, and the soil to water ratio (S / W) was 1:1 by mass.
[0100] The results of the anti-abrasion performance test are as follows: Figure 6 , Figure 7 As shown, the polyurea layer corresponding to PUA and the hard iron layer corresponding to IS have lower wear rates than the other two.
[0101] In the third type of experiment, different styles of bionic structures 3.2 are designed on the surface of the substrate to study the effects of different bionic structures 3.2 on the wear resistance of the surface wear-resistant layer.
[0102] In order to speed up the abrasion test efficiency and reduce the abrasion test time, the flow rate of the debris flow in the test was 5 m / s, the particle content was 30.3%, and the density was 1.5 g / cm 3 Compared with the gravel with an average particle size of 16.6 mm used in the first and second tests, the abrasive in the third test used 6 mm steel balls to simulate the fixed particles in the debris flow, further reducing the abrasion test time. The total test time was 24 h.
[0103] like Figure 8 , Fig. 9 , Fig.10 , Fig.11 As shown, a boss structure, a wire groove structure, a ball groove structure, and a net groove structure are designed on the surface of the substrate. Figure 8 (a) Fig. 9 (a) Fig.10 (a) Fig.11 (a), from a top view, the boss structure and the line groove structure form parallel stripe patterns on the substrate surface, the ball groove structure forms a pattern formed by a matrix arrangement of several circular patterns on the substrate surface, and the mesh groove structure forms a pattern formed by a matrix arrangement of several square patterns on the substrate surface. Figure 8 (b) Fig. 9 (b) Fig.10 (b) Fig.11 (b), from the side view, the convex strips in the boss structure are higher than the surface profile of the substrate, the square strips in the line slot structure, the hemispheres in the ball slot structure, and the square blocks in the mesh slot structure are all embedded in the substrate and the top surface is flush with the substrate surface, forming a smooth substrate surface profile. The height of the convex strips, the height of the square strips, the height of the round bottom of the hemisphere, and the height of the square block are the block height D1, the distance between adjacent convex strips, the distance between adjacent square strips, the distance between adjacent hemispheres, and the distance between adjacent square blocks are the block spacing D2, and the width of the convex strips, the width of the square strips, the diameter of the circular surface of the hemisphere, and the width of the square block are the block width D3.
[0104] First, in order to study the abrasion resistance of boss structure, line groove structure, ball groove structure and net groove structure, a comparative test group 1 was designed. Four types of bionic structures 3.2, namely boss structure, line groove structure, ball groove structure and net groove structure, were processed on the surface of the 4cm*4cm*16cm base sample according to the structural parameters of "block height D1=5mm, block spacing D2=8mm, block width D3=8mm" to form four groups of samples: Convex, Parallel, Circle and Net. At the same time, the sample Ref.3 without surface wear-resistant layer was used as the reference group. The parameters of the samples with different types of bionic structures 3.2 are shown in Table 6: Table 6 Parameters of specimens with different types of bionic structures After setting the bionic structures 3.2 of different morphologies according to the same structural parameters, the projected areas of the polyurea layer in the top view are different, that is, the surface areas of the bionic structures are different, and the proportions of the substrate surface covered by different bionic structures 3.2 are also different.
[0105] After 24 hours of testing, the mass loss of the samples No. Ref.3, Convex, Parallel, Circle, and Net in Table 6 is as follows: Fig.12 As shown in Figure 6, the mass loss of the sample without surface wear-resistant layer is significantly higher than that of other samples with bionic structure 3.2, while the mass losses of samples Convex, Parallel, and Net are similar and relatively small; on the other hand, the compressive strength and flexural strength test results of the samples No. Ref.3, Convex, Parallel, Circle, and Net in Table 6 are shown in Figure 6. Fig.13 As shown, from Fig.13 (a) Schematic diagram of compressive strength test results and Fig.13 (b) Comparative analysis of the bending strength test results shown in the figure shows that the compressive strength and bending strength of the sample Convex are relatively excellent.
[0106] like Fig.16 The figure shows the principle diagram of solid particles in debris flow scouring the surface of sample Ref.3, sample Convex, sample Parallel, sample Circle, and sample Net. Fig.16 (a) corresponds to the surface abrasion principle of sample Ref.3. Fig.16 (b) Fig.16 (c) Fig.16 (d) Fig.16 (e) Schematic diagram of the surface abrasion principles of the bionic structure samples Convex, Parallel, Circle, and Net.
[0107] After 24 hours of testing, the abrasion morphologies of the above five types of samples are as follows: Fig.17 As shown, Fig.17 (a) Fig.17 (b) Fig.17 (c) Fig.16 (d) Fig.17 (e) shows the abrasion morphology of the sample Ref.3, sample Convex, sample Parallel, sample Circle, and sample Net, respectively, with obvious differences. Since the circular patterns in the ball groove structure are arranged horizontally at intervals, the uncovered substrate surface between the two circular patterns is directly exposed to the abrasion conditions of the debris flow and is prone to abrasion; and the bionic treatment area of the ball groove structure is the smallest, 15.1cm 2 , accounting for only 23.6% of the sample surface area. The bionic treatment areas of the boss structure, wire slot structure, and mesh slot structure are 38.4 cm 2 、38.4 cm 2 and 32 cm 2, accounting for 60%, 60% and 50% of the total area of the sample respectively. Therefore, after the bionic treatment of the boss structure, the wire groove structure and the mesh groove structure, the surface wear-resistant layer has less abrasion and better wear resistance.
[0108] Secondly, in order to study whether the relationship between the polyurea block size and the debris flow particle size D4 in the four types of bionic structures 3.2 affects the anti-abrasion ability, a comparative test group 2 was designed: according to the precondition that the particle size in the abrasive is 6 mm, the block spacing D2 and block width D3 in the Convex specimen and Parallel specimen structural parameters are designed to be 4 mm, 6 mm, and 8 mm, and the other structural parameters are the same. After 24 hours of abrasion, the anti-abrasion performance test, compressive strength test, and flexural strength test are carried out. Fig.14 As shown in the figure, when D2=D3=6mm and D2=D3=8mm, the mass loss is similar and significantly smaller than that of the sample with D2=D3=2mm. Fig.15 As shown, its Fig.15 (a) shows the compressive strength test results. Fig.15 (b) shows the test results of bending strength. Comparative analysis shows that when the block spacing D2 and the block width D3 are 4 mm, 6 mm, and 8 mm respectively, the compressive strengths of the Convex specimen and the Parallel specimen are similar and both tend to increase; the bending strength of the Convex specimen is significantly greater than that of the Parallel specimen and increases gently, while the bending strength of the Parallel specimen first decreases and then increases.
[0109] Based on the design concept of comparative test group 1 and comparative test group 2, different combinations of structural parameter values were designed through the control variable method for testing, and the conclusions were drawn: When the bionic structure 3.2 is only different in morphology and has the same values of structural parameters, the boss structure used as the surface wear-resistant layer of the bionic structure 3.2 has excellent comprehensive performance in wear resistance, compressive strength and bending strength; When the height D1 of the block in the bionic structure 3.2 and the average particle size D4 of the debris flow particles satisfy: D1 ≥ D4 / 1.2, the surface wear-resistant layer having the bionic structure 3.2 has excellent comprehensive performance in wear resistance, compressive strength and bending strength; When the spacing D2 and the width D3 of the blocks in the bionic structure 3.2 satisfy: D2≤2D3, the surface wear-resistant layer of the bionic structure 3.2 has excellent comprehensive performance in wear resistance, compressive strength and bending strength; When the spacing D2 between the blocks in the bionic structure 3.2 and the average particle size D4 of the debris flow particles satisfy: D2≥D4, the surface wear-resistant layer having the bionic structure 3.2 has excellent comprehensive performance in wear resistance, compressive strength and bending strength.
[0110] The other parts of this embodiment are the same as those of Embodiment 1, and thus will not be described in detail.
[0111] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification or equivalent change made to the above embodiment according to the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for reinforcing and repairing a debris flow protection structure, characterized in that: First, evaluate the surface abrasion depth of the protective structure to formulate a reinforcement and repair strategy; according to the reinforcement and repair strategy, when implementing the repair project, clean the area to be constructed and pour the matrix reinforcement material into the area to be constructed so that it can penetrate into the base material of the protective structure to repair or enhance the ability to resist overall structural damage; then add a surface wear-resistant layer on the surface of the base material to repair or enhance the ability to resist surface damage.
2. The method for reinforcing and repairing a debris flow protection structure according to claim 1, characterized in that: The surface wear-resistant layer is made of a hard iron sheet, and during construction, the hard iron sheet is pasted on the surface of the substrate.
3. The method for reinforcing and repairing a debris flow protection structure according to claim 1, characterized in that: The surface wear-resistant layer is formed by curing polyurea coating. During construction, the polyurea coating is sprayed on the surface of the substrate, or a number of polyurea blocks are fixed on the surface of the substrate in a bionic arrangement to form a bionic structure.
4. The method for reinforcing and repairing a debris flow protection structure according to claim 3, characterized in that: The bionic structure adopts a boss structure, a wire slot structure, a ball slot structure or a net slot structure; The boss structure is composed of a plurality of parallel long convex strips that are raised relative to the surface of the substrate, and the convex strips are arranged horizontally relative to the flow direction of the debris flow; the convex strips in this structure are polyurea blocks pressed by a mold; The wire trough structure is composed of a plurality of parallel long square strips that are recessed relative to the surface of the substrate, and the square strips are arranged horizontally relative to the flow direction of the debris flow; The square strips in this structure are polyurea blocks pressed through a mold; The ball groove structure is formed by arranging a plurality of hemispherical bodies in a matrix which are recessed relative to the surface of the substrate; the hemispherical bodies in this structure are polyurea blocks pressed by a mold; The mesh structure is formed by arranging a plurality of square blocks in a matrix which are recessed relative to the surface of the substrate; the square blocks in this structure are polyurea blocks pressed by a mold.
5. The method for reinforcing and repairing a debris flow protection structure according to claim 4, characterized in that: When any of the bionic structures such as the line groove structure, the ball groove structure and the net groove structure is used for surface structuring treatment, a groove structure is reserved on the surface of the substrate according to the structure and arrangement of the polyurea blocks, and then the polyurea blocks are embedded in the groove structure.
6. The method for reinforcing and repairing a debris flow protection structure according to claim 1, characterized in that: The matrix reinforcement material comprises coarse aggregate and mortar; the gradation distribution of the coarse aggregate conforms to the Andreasen & Andersen model, and the distribution modulus q is 0.19; the mortar consists of P·I type 42.5 grade silicate cement, microsilica fume, ISO standard sand, steel fiber, water reducer and water.
7. The method for reinforcing and repairing a debris flow protection structure according to claim 6, characterized in that: The steel fiber is copper-plated steel fiber or end-hook steel fiber, and the amount of the steel fiber is 1% of the total volume of the matrix reinforcement material.
8. The reinforcement and repair material for debris flow protection structure is characterized by: The repair material includes a matrix reinforcement material and a surface wear-resistant material; The matrix reinforcement material can penetrate into the base material of the protective structure to enhance the resistance and reduce the overall structural damage caused by debris flow impact and environmental factors; The surface wear-resistant material can be covered on the surface of the protective structure to enhance the resistance and reduce the surface damage caused by the scouring of particles in the debris flow.
9. A method for predicting the erosion depth of a debris flow protection structure, characterized in that: The abrasion depth is estimated according to the structural density of the debris flow protection structure, the duration of the debris flow, the abrasion coefficient and the correction coefficient, so as to implement the reinforcement and repair method of the debris flow protection structure as claimed in claim 1; The abrasion depth is estimated according to formula 11: (Formula 11) In the formula, E h Indicates the abrasion depth, unit: m; k Indicates the abrasion coefficient, which indicates the abrasion mass loss per unit area per unit time, unit: kg / h / m 2 ; ρ c Indicates structural density, unit: kg / m 3 ; t Indicates duration, unit: h; a Indicates the correction factor.
10. The method for predicting the abrasion depth of a debris flow protection structure according to claim 9, characterized in that: The value of the correction coefficient is calculated by two sets of parameters related to the volume content, density, particle size and flow velocity of solid particles in the debris flow parameters and the laboratory test parameters; The correction coefficient is calculated according to formula 10: (Formula 10) In the formula, a It represents the correction coefficient, which is used to adjust the difference between the indoor abrasive parameters and the actual debris flow parameters during the abrasion coefficient test; V s Represents the volume content of solid particles in debris flow, unit: %; ρ s Indicates the density of solid particles in debris flow, unit: kg / m 3 ; D s Indicates the particle size of the solid phase particles of debris flow, unit: m; u s It indicates the flow velocity of solid particles in debris flow, unit: m / s; V o Indicates the volume content of abrasive solid particles, unit: %; ρ o Indicates the density of abrasive solid particles, unit: kg / m 3 ; D o Indicates the particle size of abrasive solid particles, unit: m; u o Indicates the flow rate of abrasive solid particles, unit: m / s.
Citation Information
Patent Citations
Double-shaft rolling type wear resistance testing device and method capable of simulating channel section form
CN113390745A
Method for rehabilitating concrete surface injury using high-strength abrasion-proof basalt fibre mortar
CN101235673A
Comprehensive treatment measure for preventing and treating channel debris flow starting and design method thereof
CN113322900A
Distribution calculation method for abrasion depth of debris flow drainage groove
CN114357805A
Debris flow drainage groove abrasion section damage repairing method
CN114541337A